Frequency of Dicarboximide Resistant Strains of Botrytis cinerea in South African Table Grape Vineyards and Influence of Spray Schedules on Resistant Sub-Populations - Fourie, P.H.; Holz, G. (South African Journal of Enology and Viticulture, 2017)
Between 1993 and 1995, 1139 isolates of Botrytis cinerea were collected from table grape vineyards in the Western and Northern Cape provinces and tested for sensitivity to dicarboximides (vinclozolin) and benzimidazoles (carbendazim). Overall the frequency of resistance to vinclozolin and carbendazim averaged 9,4 and 11,9%, respectively. Ninety-seven percent of the vinclozolin-resistant isolates were dual resistant to carbendazim. Fifty-nine percent of the isolates were from the Hexriver region; of these 7,7% were vinclozolin, and 12,6% carbendazim resistant. The Paarl region had the highest resistance incidence (37,7% vinclozolin and 41,5% carbendazim resistant). Only two of the 191 isolates tested from the Orange River region were vinclozolin resistant. ED50 values of ultra-low-level and low-level dicarboximide-resistant isolates ranged from 0,843 to 1,834 and 2,053 to 5,129 μg vinclozolin/ml, respectively. Vinclozolin-resistant strains were not abnormally osmotically sensitive. Monitoring of changes in the frequency of resistance in 10 commercial vineyards under high-, medium- and low-schedule dicarboximide programmes from 1993-1995 showed that the resistance frequency fluctuated from low (average 12,7% ) during the winter to high (average 55,8 % ) during the growing season. Maximum levels of dicarboximide resistance were recorded during bunch closure. Distinct differences were, however, observed in the resistance frequency in individual vineyards. In four high-schedule dicarboximide vineyards resistance frequencies increased early in the season, prior to any dicarboximide applications. This finding suggests dual resistance between broad-spectrum fungicides and dicarboximides.